Avant que le Crucifié ne «parle» à S. François : les mentions de crucifix parlants antérieurs à celui de San Damiano à Assise - Sansterre, Jean-Marie (Analecta Bollandiana, 2011)
The article is devoted to texts which mention talking crucifixes prior to the famous miracle of the cross of Saint Damianus at Assisi which is related by Thomas of Celano in his second Vita of St. Francis (1246-1247). It deals principally with crucifixes which are considered to have actually spoken and not with dreams about speaking crucifixes. The earliest account is of a crucifix of the Niedermünster convent at Regensburg which is related in the Vita Erhardi episcopi Bavarici (BHL 2590) written between 1054 and 1073. It goes back to a tradition of 973-994 and is thus relatively close to the first known miracle of a crucifix (921). It therefore did not take long before speaking became a part of the manifestations of Christ’s miraculous presence in his images. However, Thomas of Celano’s account marks a new stage by its stress on the personal relation of the crucified Lord with the saint whom he is addressing.